Sound velocity and parameter of nonlinearity of a ternary mixture consisting of water, vapor and dry air - PERELOMOVA, A. (Archives of Acoustics, 2006)
Acoustic properties of a binary mixture consisting of a liquid being in phase equilibrium with its vapor and a ternary mixture including a binary one and a neutral gas are considered. Detailed calculations of the excess entropy of a ternary mixture in terms of its excess pressure and density are carried out with accuracy up to quadratic nonlinear terms. That allows to estimate the small signal sound velocity and the parameter of nonlinearity B/A of the mixture as a whole. The only assumption is that the vapor and the neutral gas are ideal gases. As an example, the ternary mixture consisting of air and water being in equilibrium with its vapor is considered. Two different kinds of ternary mixtures are considered, one associated with the mixture in which the vapor and air occupy a mutual volume, and another associated with a mixture in which the gases occupy the separate volumes.